Are we optimizing medical students’ preparation for clerkship? A content analysis of narrative comments on clinical skills during preclinical training - Bergeron, Linda; Blanchette, Patricia; Chakroun, Molk; Boileau, Élisabeth; Boulais, Isabelle; Chamberland, Martine; St-Onge, Christina (Canadian Medical Education Journal, 2025)
Introduction: The progression from preclinical medical training to clerkship is a pivotal yet steep transition for medical students. Effective feedback on clinical skills during preclinical training can better equip students for clerkship and allows time for them to address difficulties promptly. The goal of this study was to explore whether and how narrative comments at this stage were being leveraged to achieve this transition. Methods: We conducted a content analysis to categorize narrative comments on the clinical skills of two cohorts of third-year preclinical students at one academic institution. Results: Teachers made narrative comments for 272 students. Each comment was divided into analysis units (n = 1,314 units). Comments were either general (n = 187) or focused on attitude (n = 628), knowledge and cognitive processes (n = 357), or clinical reasoning (n = 142). They were abundantly positive (n = 1,190) and marginally negative (n = 39). Few (6%) contained suggestions for improvement. Discussion: In this study, narrative comments on clinical skills before clerkship seemed minimally helpful, as they were overwhelmingly positive and seldom offered suggestions. This could suggest missed opportunities for early interventions. Pre-clerkship narrative comments could potentially be optimized by increasing emphasis on clinical reasoning, addressing challenges early and providing actionable steps for improvement.